Intellectual values and epistemological understanding of middle school students in Indonesia - Ika Andrini Farida; Dewi Retno Suminar; Nur Ainy Fardana Nawangsari (HUMANITAS: Indonesian Psychological Journal, 2020)
Engaging in intellectual activities and seek new knowledge is critical for Indonesian students. However, most learning activities in elementary and secondary schools in Indonesia are centered on rote learning. This study aimed to provide an initial description of how middle school students in Indonesia value intellectual activities and describe the level of epistemological understanding that underlie how they value intellectual activities. Sixty-eight middle school students were involved in this study by giving their responses to intellectual values questions. Descriptive analysis was conducted to examine the percentage of participants who endorse discussion. Additionally, the reasons for endorsing discussion were also examined to determine the epistemological understanding level. The percentage of participants that endorse discussion in question one, two, and three was 71%, 47%, and 50%, respectively. While 24% of participants consistently endorsed discussion in all three questions. Most students gave reasons that indicate absolutist or multiplist level of an epistemological understanding. Very few reasons can be categorized into the evaluativist level. Students seem to believe that discussion is important to do to solve the problems. Most students have yet to perceive the intellectual activity as an essential tool to enhance their understanding and acquire new knowledge, as an evaluativist would.